Empowers Students' Communication Skills Through ‘News Flash!’ - Noraisah Nurul Fatwa, Mohd Razali; Nur Syafawati, Sabuan; Ezihaslinda, Ngah (UMPSA, 2025)
In alignment with its ambitious mission to cultivate students who are not only confident, and articulate but also exceptionally well-rounded, the Centre for Modern Languages (CML), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), on 24 April 2025 carried out a transformative community service programme titled Game On: English Edition at Maktab Rendah Sains MARA (MRSM) Kuantan.